The Italian romance epic in the age of humanism the matter of Italy and the world of Rome - Everson, J. E. (Jane E.) (Oxford University Press, 2001)
The romance of chivalric epic was the most popular form of literature in Renaissance Italy. This book shows how it owed its appeal to a successful fusion of traditional, medieval tales with the newer cultural themes.